The Effectiveness of Family Health Counseling Training on Knowledge and Counseling Skills for BIKKSA Cadre in Lamongan Regency - Nurafifah, Dian; Saifudin, Moh (Universitas Islam Lamongan, 2022)
Various problems often arise in the family that affect the health of family members both physically and psychologically so that counseling is needed to the right person. Ideally, counseling is carried out by professionals, but due to the limited number of counselors, the counseling is carried out by BIKKSA cadres who are appointed and volunteer as lay counselors. Unfortunately, the cadres do not have the ability to explore problems and solve problems. The study was conducted to determine the effectiveness of family health counseling training on the knowledge and counseling skills of BIKKSA cadres. Quasy experimental research design (one group pretest and posttest design). The sample is 27 BIKKSA cadres in Lamongan Regency. The research instrument is a questionnaire. Data collection by observation. Analysis of the data using the Wilcoxon test with = 0.05. The results showed the value of p = 0.000. Based on this research, it is known that family counseling training is effective in increasing the knowledge and counseling ability of BIKKSA cadres.